Analysis of Briquettes Characteristics Made of Oil Palm Frond Waste and Sugarcane Bagasse with Tapioca Starch Adhesive - Agam Muarif; Rizka Mulyawan; Ahmad Fikri; Desvina Yulisda; Dedi Sutarma; Intan Rukmana; Ahmad Pane (LPPM Universitas Malikussaleh, 2024)
Oil palm frond waste and sugarcane bagasse are high-fiber biomass materials that can be converted into alternative energy sources like briquettes. The carbonization method is used to create charcoal briquettes, converting raw organic materials into carbon. The produced charcoal is mixed with a adhesive and molded into cylindrical or block shapes. This study aims to determine the characteristics of briquettes with varying compositions of palm fronds and bagasse (50:50 ; 40:60 ; 30:70 ; 20:80 ; 10:90 (b/b)) and different tapioca starch adhesive amounts (40% ; 45% ; 50% ; 55% (v/b)). In this study, tests were conducted on moisture content, ash content, calorific value, and combustion rate. The research findings indicate that the best-quality charcoal briquettes were produced by combining sugarcane bagasse and palm fronds in a 50:50 ratio with a adhesive containing 40% tapioca starch. These briquettes have the following properties: moisture content of 4.4545%, ash content of 4.62021%, combustion rate of 0.2283 g/min, and calorific value of 6,232.67 cal/g. These results indicate that the briquettes made from a mixture of oil palm frond waste and sugarcane bagasse using tapioca starch as a adhesive have met the SNI 01-6235-2000 standard criteria.